Dietary betaine reduces plasma homocysteine concentrations and improves bone strength in laying hens. Issue 4 (4th July 2021) - Maidin, M. B. M.; McCormack, H. A.; Wilson, P. W.; Caughey, S. D.; Whenham, N.; Dunn, I. C.
ABSTRACT: 1. This study tested the hypothesis that the methyl-donor properties of betaine could reduce homocysteine concentrations, which has been recognised in a previous genetics study to be linked to bone quality. This was combined with phytase treatment, as phosphorus is critical for bone mineralisation. 2. Using a 2 × 2 factorial arrangement, a total of 1920 Lohmann LSL-lite chickens housed as 24 replicates of 20 chickens were fed one of four diets containing dietary betaine (0 or 1000 mg/kg) and phytase (300 or 1000 FTU/kg) from one day old until end-of-lay. Blood and bone samples were collected at 45 and 70 weeks of age. 3. Hens fed betaine had lower plasma homocysteine level (P < 0.05), higher tibia breaking strength (P < 0.05) and higher tibia bone density (P < 0.05). 4. Egg production and quality was excellent throughout the study and were not affected by the dietary treatments. 5. The addition of dietary betaine was successful at reducing plasma homocysteine concentrations and improving bone strength in laying hens, which could be used as an intervention to alleviate welfare concerns.